Two regions of the herpes simplex virus type 1 UL42 protein are required for its functional interaction with the viral DNA polymerase. - Monahan, S J (1993)
Two essential gene products of herpes simplex virus type 1, the viral DNA polymerase (pol) and UL42, its accessory protein, physically and functionally interact to form the core of the viral DNA replication complex. Understanding this essential interaction would provide a basis from which to develop novel anti-herpesvirus agents. We previously have shown that when coexpressed in an in vitro transcription-translation system, UL42 stimulates pol activity (M. L. Gallo, D. I. Dorsky, C. S. Crumpacker, and D. S. Parris, J. Virol. 63:5023-5029, 1989). By analyzing various insertion, deletion, and frameshift mutations of UL42 in this system, we found the C-terminal 149 amino acids to be dispensable for the ability of the protein to stimulate pol activity. In addition, two distinct internal regions of UL42 were found to be required for pol stimulation. Regions I and II were defined to lie between amino acid residues 129 and 163 and between residues 202 and 337, respectively. When physical association was examined with antibody to UL42, pol was found to coimmunoprecipitate to the same level when expressed with a UL42 mutant protein lacking region I as that with wild-type UL42. Thus, mere physical association is insufficient for stimulation of pol activity. Deletion of region II reduced or eliminated coimmunoprecipitation with pol. Interestingly, an antibody to pol specific for residues 1216 to 1224 coimmunoprecipitated UL42 when both proteins were synthesized in a baculovirus expression system but not in rabbit reticulocyte lysates. These results indicate that (i) at least a portion of the region recognized by the pol antiserum may be accessible in the pol-UL42 heterodimer and (ii) immunoprecipitation results for products made in different expression systems may vary. Thus, at least two distinct regions of UL42 are essential for functional interaction with pol. Moreover, these results point to a UL42 region I function other than physical association with pol.